2014
DOI: 10.1007/s10549-014-3088-2
|View full text |Cite
|
Sign up to set email alerts
|

Digital compared to screen-film mammography: breast cancer prognostic features in an organized screening program

Abstract: Our previous study found cancer detection rates were equivalent for direct radiography compared to screen-film mammography, while rates for computed radiography were significantly lower. This study compares prognostic features of invasive breast cancers by type of mammography. Approved by the University of Toronto Research Ethics Board, this study identified invasive breast cancers diagnosed among concurrent cohorts of women aged 50-74 screened by direct radiography, computed radiography, or screen-film mammog… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 25 publications
0
1
1
Order By: Relevance
“…This large study of concurrent cohorts reported results different from ours concerning CR; they show a statistically significant 21% lower detection rate and no statistically significant difference in recall rate for CR compared to SFM. Moreover, they found that cancers detected by CR compared to SFM were significantly more likely to be lymph node positive and have a higher stage [35]. In our data, there was little or no difference in detection rate and higher recall rate in CR compared to SFM.…”
Section: Discussioncontrasting
confidence: 45%
“…This large study of concurrent cohorts reported results different from ours concerning CR; they show a statistically significant 21% lower detection rate and no statistically significant difference in recall rate for CR compared to SFM. Moreover, they found that cancers detected by CR compared to SFM were significantly more likely to be lymph node positive and have a higher stage [35]. In our data, there was little or no difference in detection rate and higher recall rate in CR compared to SFM.…”
Section: Discussioncontrasting
confidence: 45%
“…Evidence from large randomized controlled trials and concurrent cohort studies suggest that DR is at least equivalent to SFM in cancer detection and may offer improved detection for ductal carcinoma in situ (DCIS) and among young women with dense breasts (3-10). However, our previous studies have shown that breast screening with CR mammography may result in significantly lower cancer detection and has the potential for delayed diagnosis (10,11).…”
Section: Study Populationmentioning
confidence: 99%